2017
DOI: 10.1017/s1355617717000236
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Longitudinal Associations Between Reaction Time Intraindividual Variability and Age-Related Cognitive Decline or Impairment, Dementia, and Mortality

Abstract: Objective: Intraindividual variability (IIV) in reaction time refers to the trial-to-trial fluctuations in responding across a given cognitive task. Cross-sectional research suggests that IIV increases with normal and neuropathological ageing and it may serve as a marker of neurobiological integrity. This raises the possibility that IIV may also predict future cognitive decline and, indeed, neuropathology. Therefore, we conducted a systematic review to address these issues. It is well established that adult ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 53 publications
6
80
0
1
Order By: Relevance
“…A contrary view posits that variability in reaction times, whether trial to trial variability within a task (as in RT SD) or task to task variability (such as test-retest reliability), do not only reflect measurement error but are indicators of systematic underlying, usually pathological, processes ( Bunce, MacDonald, & Hultsch, 2004 ). The proponents of this theory point to increased RT variability associated with a number of neurological conditions ( Hetherington, Stuss, & Finlayson, 1996 ) and to studies where RT SD is more predictive than mean RT ( Haynes, Bauermeister, & Bunce, 2017 ). The results here are not consistent enough across causes to provide evidence either for or against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…A contrary view posits that variability in reaction times, whether trial to trial variability within a task (as in RT SD) or task to task variability (such as test-retest reliability), do not only reflect measurement error but are indicators of systematic underlying, usually pathological, processes ( Bunce, MacDonald, & Hultsch, 2004 ). The proponents of this theory point to increased RT variability associated with a number of neurological conditions ( Hetherington, Stuss, & Finlayson, 1996 ) and to studies where RT SD is more predictive than mean RT ( Haynes, Bauermeister, & Bunce, 2017 ). The results here are not consistent enough across causes to provide evidence either for or against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…IRV is particularly advantageous in that it is a relatively simple measurement that controls for overall speed of responding (e.g., it can be calculated as the standard deviation of RT divided by mean RT). IRV may provide a better metric of cognitive impairment than other neuropsychological test measures, such as standardized cognitive or psychomotor tasks (Haynes et al, 2017;Balota et al, 2010;Cherbuin et al, 2010) or simple RT (Dixon et al, 2007). Attentional deficits are commonly reported in attention deficit hyperactivity disorder (ADHD) during both laboratory tasks and in daily life (Klein et al, 2006;Leth-Steensen et al, 2000;Russell et al, 2006;Tamm et al, 2012;Barkley, 1997;Sonuga-Barke and Castellanos, 2007), with higher IRV commonly reported in ADHD (Kuntsi and Klein, 2011;Castellanos et al, 2006;Mullins et al, 2005;Kofler et al, 2013;Vaurio et al, 2009;Castellanos et al, 2005;Bellgrove et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that RT IIV was predictive of declining fluid abilities including memory, speed, reasoning, and fluency, whereas no change was observed in verbal performance (reflecting crystalized ability) (Bielak et al, 2010). A recent systematic review verified cognitive associations with RT IIV, and that inconsistency precedes cognitive decline in aging (Haynes, Bauermeister, & Bunce, 2017). Of note, previous studies have not consistently included common neuropsychological tests from clinical practice, nor have they examined the RT parameters that contributed to these associations.…”
Section: Introductionmentioning
confidence: 99%